The Evolution of the Constitutional Control in France from Political to Judicial Control - Mawlud, Muhammed Omer (Journal of Legal and Political Studies, 2022)
Undoubtedly that principle of legality based on that everyone in the state, weather rulers or ruled be subject to the provisions of the constitution, and for the purpose of subjecting the various authorities in the state to the provisions of the constitution a mechanism must be provided, and this mechanism is the constitutional control of laws, it is customary to call this mechanism political control if the body doing it is political body, and it is named judicial control if the courts doing it.
Keywords: constitutio; authorities; customary; constitutional contro; political control